Total Phenolics and Flavonoid Content of Maceration-based Purslane (Portulaca oleracea) Extract - Saefur Rohman; Anisah Qurrotu Aini (Future Science, 2022)
Purslane (Portulaca oleracea) is an underutilized plant that is commonly known as a weed; yet possesses high potential for its utilization as an alternative crop for medicinal purposes. This is due to Purslane's nutrient-rich status which, aside from its omega-3, is also a rich source of vitamins, minerals, and bioactive compounds such as phenolics and flavonoids. This work investigated the bioactive properties of Purslane extract in terms of Total Phenolics Content (TPC) and Total Flavonoid Content (TFC). The extract was prepared in ethyl acetate, ethanol, and n-hexane solvent using the maceration method. The results showed similar results in which the highest TPC and TFC were found in ethyl acetate extract at 14.74 ?g GAE/g and 11.56 ?g QE/g. This result showed the potential for further utilization of Purslane for medicinal purposes.